Mechanically-reinforced creep-resistant polyester fiber and preparation method thereof
By pre-forming the furan ring in the polyester fiber and forming a covalent crosslinking network with bismaleimide, the problem of creeping in polyester fibers during long-term applications is solved, and the effect of significantly improving mechanical properties and creep resistance is achieved.
Patent Information
- Application Number
- CN202411959979.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-14
AI Technical Summary
Polyester fibers are prone to creep during long-term applications, especially when the temperature is higher than the glass transition temperature of the polyester, which affects its application in many fields.
The furan ring is generated by pre-reacting in the backbone of the polyester molecule and blended with bismaleimide at the melt spinning stage to form a covalent crosslinking network structure to inhibit the movement of the molecular chain.
It significantly improves the mechanical properties and creep resistance of polyester fibers, reduces creep phenomenon, and does not affect the spinning properties and melt processing properties of the fibers.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyester modification, in particular to a mechanically reinforced creep-resistant polyester fiber and a preparation method thereof. Background Art
[0002] Polyester fiber is a textile fiber made from polyethylene terephthalate (PET) as a matrix. It is currently the largest variety of textile fibers and has become the most important source of textile fibers in the world. The molecular structure of polyester gives the fiber good comprehensive properties, such as high modulus, impact resistance and chemical corrosion resistance. However, polyester fiber will inevitably deform during long-term use, that is, creep. Creep refers to the phenomenon that the deformation of polymers gradually increases with time under a certain temperature and constant stress. It is currently one of the main problems of fibers. Although the highly oriented crystalline form of polyester molecular chains makes it difficult for fiber molecular chains to slip, creep will still occur under long-term use, especially when the ambient temperature is higher than the glass transition temperature of polyester, the creep will be more severe, which affects the application of polyester fibers in many fields. Generally, the creep resistance of polyester materials can be improved by cross-linking molecular chains, forming interpenetrating networks and increasing molecular weight.
[0003] Related patents such as CN103556291A disclose that fluorinated epoxy compounds and carbodiimide stabilizers form hydrogen bonds in polyester molecular chains to improve the creep resistance of polyester. However, the hydrogen bond energy is relatively small compared to covalent bonds, and the improvement effect is limited.
[0004] Existing patent CN115305596A discloses a method of adding anthracene-containing functional groups during the polyester thickening process to obtain a thickening polyester containing anthracene functional groups in the side chain, and adding bismaleimide to form dynamic crosslinking to improve creep resistance. However, the high steric hindrance functional groups in the side chain often cause the spinnability of the polyester to deteriorate, especially fine denier yarns.
[0005] The existing patent CN115787132A discloses a method of preparing a linear polyester containing unsaturated end groups by reactive blending, which is then melt-blended and spun with a branched polyester containing unsaturated end groups, and then cross-linked by electron beam irradiation to prepare creep-resistant polyester industrial yarn. However, its preparation process is still relatively complicated, and multiple thermal processing will affect the quality of polyester.
[0006] From the above disclosed technologies, the current polyester creep resistance is mainly based on reactive blending to form a cross-linked network. Therefore, there is a need for a modification method that can effectively improve the mechanical strength and creep resistance of polyester fibers without affecting their spinning. Summary of the invention
[0007] The purpose of the present invention is to provide a mechanically enhanced creep-resistant polyester fiber and a preparation method thereof, so as to simplify the modification path and efficiently develop functional polyester fiber products on the basis of achieving the creep resistance of the polyester fiber.
[0008] To achieve the above object, the present invention provides the following technical solutions:
[0009] A method for preparing a mechanically reinforced creep-resistant polyester fiber comprises the following steps:
[0010] Step 1, terephthalic acid and furan units are mixed by mole ratio to obtain a first composition, wherein the furan units are 2,5-furandicarboxylic acid or dimethyl 2,5-furandicarboxylate, and a dibasic acid and a diol are mixed by mole ratio to obtain a second composition;
[0011] Step 2, mixing the first composition, the second composition and the titanium / antimony composite catalyst, mixing evenly and then subjecting the mixture to esterification and polycondensation to obtain a modified copolyester;
[0012] Step 3, subjecting the modified copolyester to vacuum drum drying, wherein the terminal carboxyl content after vacuum drum drying is 5 to 10 mol / t;
[0013] Step 4: uniformly blend the proportioned bismaleimide and modified copolyester and then perform melt spinning at a spinning temperature of 265-270° C. and a spinning speed of 600-800 m / min. After molding, the cross-linked network is constructed by cooling to obtain a mechanically enhanced creep-resistant copolyester containing a dynamic cross-linked network.
[0014] As a further solution of the present invention: the molar ratio of the terephthalic acid and furan units is 90-99:1.
[0015] As a further solution of the present invention: the molar ratio of the dibasic acid to the diol is 1.4-1.5:1.
[0016] As a further solution of the present invention: the addition amount of the titanium / antimony composite catalyst accounts for 300-600 ppm of the total mass of ethylene glycol.
[0017] As a further embodiment of the present invention: the bismaleimide is one or more of N,N'-(4,4'-methylenediphenyl)bismaleimide, N,N'-tetramethylenebismaleimide, N,N'-m-phenylenebismaleimide, 1,2-bismaleimidoethane, and N,N'-1,4-phenylenebismaleimide.
[0018] As a further solution of the present invention: the molar ratio of the added content of bismaleimide to furandicarboxylic acid is 1:0.5-1.5.
[0019] As a further solution of the present invention: the fiber made of the mechanically reinforced creep-resistant copolyester has a breaking strength of 4.0-8.0 cN / dtex and an initial modulus of 100-200 cN / dtex. A creep test is carried out under the conditions of a temperature of 25°C, a relative humidity of 65%, a constant tension of 2.00 cN / dtex and a time of 10 min, and the elongation of the creep-resistant fiber is less than 1%.
[0020] As a further solution of the present invention: the temperature of the vacuum drum drying treatment is 90-110°C.
[0021] As a further solution of the present invention: the vacuum drum drying treatment time is 48 hours.
[0022] The invention also discloses a mechanically reinforced creep-resistant polyester fiber, which is prepared by the above preparation method.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] 1. The present invention forms a small amount of furan ring reaction sites similar to the benzene ring structure in the polyester preparation stage, so that it does not affect the original spinnability of the polyester, and the melt quality after multiple melt processing caused by reactive blending is reduced. In addition, this in-situ polymerization can make the furan ring dispersed in the molecular chain more disordered, and there will be no additional dispersion problem caused by blending, which provides a beneficial effect for preparing homogeneous creep-resistant fibers.
[0025] 2. The furan ring reaction sites polymerized in situ in the present invention undergo a reversible cross-linking reaction with the bismaleimide added in the melt spinning process to form a covalently cross-linked network structure, thereby inhibiting the movement of the molecular chain, achieving mechanical enhancement and anti-creep effects, and being more solid than the cross-linking forms formed by hydrogen bonds, etc. At the same time, the cross-linking structure formed by the reaction of bismaleimide and furan ring to form a multi-ring will be de-cross-linked at high temperature and will not affect the melt processing performance. DETAILED DESCRIPTION
[0026] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] Embodiment 1:
[0028] A method for preparing a mechanically reinforced creep-resistant polyester fiber comprises the following steps:
[0029] Step 1, terephthalic acid and furan units are mixed by mole ratio to obtain a first composition, wherein the mole ratio of terephthalic acid and furan units is 90:1, and the furan units are 2,5-furandicarboxylic acid or 2,5-furandicarboxylic acid dimethyl ester, and a dibasic acid and a diol are mixed by mole ratio to obtain a second composition; the mole ratio of the dibasic acid and the diol is 1.4:1;
[0030] Step 2, mixing the first composition or the second composition with a titanium / antimony composite catalyst, wherein the amount of the titanium / antimony composite catalyst added is 500 ppm of the total mass of ethylene glycol, and after uniform mixing, esterification and polycondensation are performed to obtain a modified copolyester;
[0031] Step 3, subjecting the modified copolyester to vacuum drum drying treatment, wherein the vacuum drum drying treatment temperature is 110° C., the vacuum drum drying treatment time is 48 hours, and the terminal carboxyl content after the vacuum drum drying treatment is 5 mol / t;
[0032] Step 4: uniformly blend the proportioned bismaleimide and modified copolyester and then perform melt spinning at a spinning temperature of 270° C. and a spinning speed of 800 m / min. After molding, the cross-linked network is constructed by cooling to obtain a mechanically enhanced creep-resistant copolyester containing a dynamic cross-linked network.
[0033] The bismaleimide is N,N'-(4,4'-methylenediphenyl)bismaleimide; the molar ratio of the added content of the bismaleimide to furandicarboxylic acid is 1:1.2.
[0034] Tests show that the fiber made of the mechanically reinforced creep-resistant copolyester has a breaking strength of 8.0 cN / dtex and an initial modulus of 150 cN / dtex. The creep test is carried out under the conditions of a temperature of 25°C, a relative humidity of 65%, a constant tension of 2.00 cN / dtex and a time of 10 min, and the elongation of the creep-resistant fiber is less than 1%.
[0035] Comparative Example 1: A mechanically reinforced creep-resistant polyester fiber and a preparation method thereof, which is basically the same as Example 1, except that the catalyst is replaced with an antimony catalyst of equal mass.
[0036] Tests show that the terminal carboxyl content of the modified copolyester after vacuum drum drying is 5 mol / t, the fiber breaking strength is 2.0 cN / dtex, the initial modulus is 100 cN / dtex, and the creep test is carried out under the conditions of temperature 25°C, relative humidity 65%, constant tension 2.00 cN / dtex and time 10 min, and the elongation of the fiber is 12%.
[0037] This is because the antimony catalyst used alone as a catalyst in Comparative Example 1 is insufficient to catalyze the polycondensation reaction of furan and copolyester, resulting in the molecular weight of the copolyester being difficult to meet the fiber application requirements, the fiber strength being low, and being unable to meet the anti-creep effect.
[0038] Comparative Example 2: A mechanically reinforced creep-resistant polyester fiber and a preparation method thereof, which are basically the same as Example 1, except that the catalyst is replaced with an equal mass of titanium catalyst.
[0039] Tests show that the terminal carboxyl content of the modified copolyester after vacuum drum drying is 22 mol / t, the fiber breaking strength is 4.2 cN / dtex, the initial modulus is 140 cN / dtex, and the creep test is carried out under the conditions of temperature 25°C, relative humidity 65%, constant tension 2.00 cN / dtex and time 10 min. The elongation of the fiber is 1.4%.
[0040] This is because comparative example 1 uses titanium catalyst alone as a catalyst, and its reaction activity is too high, resulting in a high overall terminal carboxyl content and color value of the modified copolyester, which does not meet the application requirements.
[0041] Embodiment 2:
[0042] A method for preparing a mechanically reinforced creep-resistant polyester fiber comprises the following steps:
[0043] Step 1, terephthalic acid and furan units are mixed by mole ratio to obtain a first composition, wherein the mole ratio of terephthalic acid and furan units is 95:1, and the furan units are 2,5-furandicarboxylic acid or 2,5-furandicarboxylic acid dimethyl ester, and a dibasic acid and a diol are mixed by mole ratio to obtain a second composition, wherein the mole ratio of the dibasic acid and the diol is 1.5:1;
[0044] Step 2, mixing the first composition or the second composition with a titanium / antimony composite catalyst, wherein the amount of the titanium / antimony composite catalyst added is 400 ppm of the total mass of ethylene glycol, and after uniform mixing, esterification and polycondensation are performed to obtain a modified copolyester;
[0045] Step 3, subjecting the modified copolyester to vacuum drum drying treatment, wherein the vacuum drum drying treatment temperature is 110° C., the vacuum drum drying treatment time is 48 hours, and the terminal carboxyl content after the vacuum drum drying treatment is 6 mol / t;
[0046] Step 4: uniformly blend the proportioned bismaleimide and modified copolyester and then perform melt spinning at a spinning temperature of 270° C. and a spinning speed of 800 m / min. After molding, the cross-linked network is constructed by cooling to obtain a mechanically enhanced creep-resistant copolyester containing a dynamic cross-linked network.
[0047] The bismaleimide is N,N'-m-phenylene bismaleimide, and the molar ratio of the added content of the bismaleimide to furandicarboxylic acid is 1:1.
[0048] Tests show that the fiber made of the mechanically reinforced creep-resistant copolyester has a breaking strength of 6.0 cN / dtex and an initial modulus of 200 cN / dtex. The creep test is carried out under the conditions of a temperature of 25°C, a relative humidity of 65%, a constant tension of 2.00 cN / dtex and a time of 10 min, and the elongation of the creep-resistant fiber is less than 1%.
[0049] Embodiment 3:
[0050] A method for preparing a mechanically reinforced creep-resistant polyester fiber comprises the following steps:
[0051] Step 1, terephthalic acid and furan units are mixed by mole ratio to obtain a first composition, wherein the mole ratio of terephthalic acid and furan units is 99:1, and the furan units are 2,5-furandicarboxylic acid or 2,5-furandicarboxylic acid dimethyl ester, and a dibasic acid and a diol are mixed by mole ratio to obtain a second composition, wherein the mole ratio of the dibasic acid and the diol is 1.4:1;
[0052] Step 2, mixing the first composition or the second composition with a titanium / antimony composite catalyst, wherein the amount of the titanium / antimony composite catalyst added is 300 ppm of the total mass of ethylene glycol, and after uniform mixing, esterification and polycondensation are performed to obtain a modified copolyester;
[0053] Step 3, subjecting the modified copolyester to vacuum drum drying treatment, wherein the vacuum drum drying treatment temperature is 110° C., the vacuum drum drying treatment time is 48 hours, and the terminal carboxyl content after the vacuum drum drying treatment is 8 mol / t;
[0054] Step 4: uniformly blend the proportioned bismaleimide and modified copolyester and then perform melt spinning at a spinning temperature of 265° C. and a spinning speed of 600 m / min. After molding, the cross-linked network is constructed by cooling to obtain a mechanically enhanced creep-resistant copolyester containing a dynamic cross-linked network.
[0055] The bismaleimide is 1,2-bismaleimidoethane, and the molar ratio of the added content of the bismaleimide to furandicarboxylic acid is 1:1.5.
[0056] Tests show that the fiber made of the mechanically reinforced creep-resistant copolyester has a breaking strength of 4.0 cN / dtex and an initial modulus of 200 cN / dtex. The creep test is carried out under the conditions of a temperature of 25°C, a relative humidity of 65%, a constant tension of 2.00 cN / dtex and a time of 10 min, and the elongation of the creep-resistant fiber is less than 1%.
[0057] Embodiment 4:
[0058] A method for preparing a mechanically reinforced creep-resistant polyester fiber comprises the following steps:
[0059] Step 1, terephthalic acid and furan units are mixed by mole ratio to obtain a first composition, wherein the mole ratio of terephthalic acid and furan units is 90:1, and the furan units are 2,5-furandicarboxylic acid or 2,5-furandicarboxylic acid dimethyl ester, and a dibasic acid and a diol are mixed by mole ratio to obtain a second composition; the mole ratio of the dibasic acid and the diol is 1.45:1;
[0060] Step 2, mixing the first composition or the second composition with a titanium / antimony composite catalyst, wherein the amount of the titanium / antimony composite catalyst added is 500 ppm of the total mass of ethylene glycol, and after uniform mixing, esterification and polycondensation are performed to obtain a modified copolyester;
[0061] Step 3, subjecting the modified copolyester to vacuum drum drying treatment, wherein the vacuum drum drying treatment temperature is 110° C., the vacuum drum drying treatment time is 48 hours, and the terminal carboxyl content after the vacuum drum drying treatment is 7 mol / t;
[0062] Step 4: uniformly blend the proportioned bismaleimide and modified copolyester and then perform melt spinning at a spinning temperature of 270° C. and a spinning speed of 800 m / min. After molding, the cross-linked network is constructed by cooling to obtain a mechanically enhanced creep-resistant copolyester containing a dynamic cross-linked network.
[0063] The bismaleimide is N,N'-1,4-phenylene bismaleimide; the molar ratio of the added content of the bismaleimide to furandicarboxylic acid is 1:0.5.
[0064] Tests show that the fiber made of the mechanically reinforced creep-resistant copolyester has a breaking strength of 4.0 cN / dtex and an initial modulus of 130 cN / dtex. The creep test is carried out under the conditions of a temperature of 25°C, a relative humidity of 65%, a constant tension of 2.00 cN / dtex and a time of 10 min, and the elongation of the creep-resistant fiber is less than 1%.
[0065]
[0066] The working principle of the present invention is: furan rings are generated by pre-reaction in the main chain of polyester molecules, and bismaleimide is blended with the furan rings in the melt spinning stage. During the cooling stage of the fiber, the bismaleimide reacts with the furan rings to gradually form a covalent cross-linked structure composed of multiple rings, thereby inhibiting the movement of the molecular chain. The prepared modified polyester fiber has significantly improved mechanical properties and anti-creep effects.
[0067] It is obvious to those skilled in the art that the present invention is not limited to the details of the above exemplary embodiments, and that the present invention can be implemented in other specific forms without departing from the spirit or basic features of the present invention. Although this specification is described in accordance with the implementation modes, not every implementation mode includes only one technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment can also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for preparing a mechanically reinforced creep-resistant polyester fiber, characterized in that: The steps include: Step 1, terephthalic acid and furan units are mixed by mole ratio to obtain a first composition, wherein the furan units are 2,5-furandicarboxylic acid or dimethyl 2,5-furandicarboxylate, and a dibasic acid and a diol are mixed by mole ratio to obtain a second composition; Step 2, mixing the first composition, the second composition and the titanium / antimony composite catalyst, mixing evenly and then subjecting the mixture to esterification and polycondensation to obtain a modified copolyester; Step 3, subjecting the modified copolyester to vacuum drum drying, wherein the terminal carboxyl content after vacuum drum drying is 5 to 10 mol / t; Step 4: uniformly blend the proportioned bismaleimide and modified copolyester and then perform melt spinning at a spinning temperature of 265-270° C. and a spinning speed of 600-800 m / min. After molding, the cross-linked network is constructed by cooling to obtain a mechanically enhanced creep-resistant copolyester containing a dynamic cross-linked network.
2. The method for preparing a mechanically reinforced creep-resistant polyester fiber according to claim 1, characterized in that: The molar ratio of the terephthalic acid and furan units is 90-99:
1.
3. The method for preparing a mechanically reinforced creep-resistant polyester fiber according to claim 1, characterized in that: The molar ratio of the dibasic acid to the diol is 1.4-1.5:
1.
4. The method for preparing a mechanically reinforced creep-resistant polyester fiber according to claim 1, characterized in that: The addition amount of the titanium / antimony composite catalyst accounts for 300-600 ppm of the total mass of ethylene glycol.
5. The method for preparing a mechanically reinforced creep-resistant polyester fiber according to claim 1, characterized in that: The bismaleimide is one or more of N,N'-(4,4'-methylenediphenyl)bismaleimide, N,N'-tetramethylenebismaleimide, N,N'-m-phenylenebismaleimide, 1,2-bismaleimidoethane, and N,N'-1,4-phenylenebismaleimide.
6. The method for preparing a mechanically reinforced creep-resistant polyester fiber according to claim 1, characterized in that: The molar ratio of the added content of bismaleimide to furandicarboxylic acid is 1:0.5-1.
5.
7. The method for preparing a mechanically reinforced creep-resistant polyester fiber according to claim 1, characterized in that The fiber made of the mechanically reinforced creep-resistant copolyester has a breaking strength of 4.0-8.0 cN / dtex and an initial modulus of 100-200 cN / dtex. A creep test is carried out under the conditions of a temperature of 25°C, a relative humidity of 65%, a constant tension of 2.00 cN / dtex and a time of 10 minutes. The elongation of the creep-resistant fiber is less than 1%.
8. The method for preparing a mechanically reinforced creep-resistant polyester fiber according to claim 1, characterized in that: The temperature of the vacuum drum drying process is 90-110°C.
9. The method for preparing a mechanically reinforced creep-resistant polyester fiber according to claim 1, characterized in that: The vacuum drum drying treatment time is 48 hours.
10. A mechanically reinforced creep-resistant polyester fiber, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Creep-resistant hydrolysis-resistance polyester FDY fiber and its preparation method
CN103556291A
Cited By
Preparation method and application of net-film-shaped copolyester hot-melt bonding material with low melting point and high stability
CN121914382A